Spatial distribution and cellular composition of adult brain proliferative zones in the teleost, Gymnotus omarorum - Valentina eOlivera-Pasilio; Daniel A Peterson; María Esmeralda Castelló (Frontiers Media S.A., 2014)
Proliferation of stem/progenitor cells during development provides for the generation of mature cell types in the CNS. While adult brain proliferation is highly restricted in the mammals, it is widespread in teleosts. The extent of adult neural proliferation in the weakly electric fish, Gymnotus omarorum has not yet been described. To address this, we used double thymidine analog pulse-chase labeling of proliferating cells to identify brain proliferation zones, characterize their cellular composition, and analyze the fate of newborn cells in adult G. omarorum. Short thymidine analog chase periods revealed the ubiquitous distribution of adult brain proliferation, similar to other teleosts, particularly Apteronotus leptorhynchus. Proliferating cells were abundant at the ventricular-subventricular lining of the ventricular-cisternal system, adjacent to the telencephalic subpallium, the diencephalic preoptic region and hypothalamus, and the mesencephalic tectum opticum and torus semicircularis. Extraventricular proliferation zones, located distant from the ventricular-cisternal system surface, were found in all divisions of the rombencephalic cerebellum. We also report a new adult proliferation zone at the caudal-lateral border of the electrosensory lateral line lobe. All proliferation zones showed a heterogeneous cellular composition. The use of short (24hs) and long (30d) chase periods revealed abundant fast cycling cells (potentially intermediate amplifiers), sparse slow cycling (potentially stem) cells, cells that appear to have entered a quiescent state, and cells that might correspond to migrating newborn neural cells. Their abundance and migration distance differed among proliferation zones: greater numbers and longer range and/or pace of migrating cells were associated with subpallial and cerebellar proliferation zones.